If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + x + (4x + 7) = 0 Reorder the terms: 7 + x + (7 + 4x) = 0 Remove parenthesis around (7 + 4x) 7 + x + 7 + 4x = 0 Reorder the terms: 7 + 7 + x + 4x = 0 Combine like terms: 7 + 7 = 14 14 + x + 4x = 0 Combine like terms: x + 4x = 5x 14 + 5x = 0 Solving 14 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 5x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 5x = 0 + -14 5x = 0 + -14 Combine like terms: 0 + -14 = -14 5x = -14 Divide each side by '5'. x = -2.8 Simplifying x = -2.8
| 2x+4=16-x | | 4w=-1 | | 5x=6y | | 2x+3=147 | | 9x^4+4x^2+1=0 | | 10x^2-4X+12=Y | | 34-5x=4x+24 | | x^2-4x=2 | | x^2-605x+1206=0 | | 8-7x=98-42x | | 2x+3-4=3x+6+6 | | x^10*e^6= | | -9x^3+18x^2-12x-8= | | 2*x*x-8=42 | | 2*x=40 | | 21=v(v-4) | | 2xx-8=40 | | 3x^2+7x+13=11 | | 2x-3=64 | | y-.8y=74 | | -5+12=17x-3-16x | | -5x*-3+8= | | 7x+1=-20 | | -5x*3+8= | | -3(x+8)-43=2-42 | | solvex^2=-7x-7 | | 22-x=2x+10 | | 22-x=2(x-5) | | -4-7=-9+x | | -3(x-4)=18 | | 2(5c-1)-1=6c+9 | | 8x+7-5x=-17 |